Ill-Formed Phrases and Ambiguity of Sentence Meaning in Students Sentence Writing - Maya Lisa Aryanti (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Being able to compile their own academic writing is one of college students’ main goals. They can generally make some good sentences yet they often make mistakes when they create phrases. The phrases which are formed wrongly will be called ill-formed phrases in this paper. This paper illustrates which ill formed phrases, the reconstruction of phrase meaning and the reconstruction of the sentence meaning.The methodology of this research is descriptive qualitative research. Syntax theories, semantics and some general linguistics theories are used in this paper. The objective of this research are to identify ill-formed phrase construction in students’ work, to reform the phrase meaning and to reform sentence meaning.The result of this paper concern to the forms of possible ill-form phrases, the phrase reconstruction in students’ works and threconstruction of the sentence meaning.